Society of Behavioral Medicine position statement: Society of Behavioral Medicine supports oral cancer early detection by all healthcare providers. Issue 4 (11th July 2018) - Peterson, Caryn E; Gordon, Sara C; Le Hew, Charles W; Dykens, J A; Jefferson, Gina D; Tampi, Malavika P; Urquhart, Olivia; Lingen, Mark; Watson, Karriem S; Buscemi, Joanna; Fitzgibbon, Marian L
Abstract : Oral cancers are increasing in the U.S. This brief calls on healthcare providers and legislators to expand awareness of risk factors, increase early detection, and support policies that increase utilization of dental services. Abstract: In response to the increasing incidence of certain oral and oropharyngeal cancers, the Society of Behavioral Medicine (SBM) calls on healthcare providers and legislators to expand awareness of oral and oropharyngeal cancer risk factors, increase early detection, and support policies that increase utilization of dental services. SBM supports the American Dental Association's 2017 guideline for evaluating potentially malignant oral cavity disorders and makes the following recommendations to healthcare providers and legislators. We encourage healthcare providers and healthcare systems to treat oral exams as a routine part of patient examination; communicate to patients about oral/oropharyngeal cancers and risk factors; encourage HPV vaccination for appropriate patients based on recommendations from the Advisory Committee on Immunization Practices; support avoidance of tobacco use and reduction of alcohol consumption; and follow the current recommendations for evaluating potentially malignant oral cavity lesions. Because greater evidence is needed to inform practice guidelines in the primary care setting, we call for more research in collaborative health and dental services. We encourage legislators to support policies that expand Medicaid to cover adult dental services, increase Medicaid reimbursement for dental services, and require dental care under any modification of, or replacement of, the Affordable Care Act.